The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/pi.3232
|View full text |Cite
|
Sign up to set email alerts
|

Poly(L‐lactic acid) with added α‐tocopherol and resveratrol: optical, physical, thermal and mechanical properties

Abstract: Poly(L-lactic acid) (PLLA) films containing various concentrations of two natural antioxidants, α-tocopherol and resveratrol, were fabricated by a melt compounding and compression molding process. The influence of the antioxidants on the optical properties such as color and UV-visible light transmission was analyzed. The thermal, mechanical, rheological and physical properties of PLLA films with added antioxidants were assessed. PLLA films with added α-tocopherol and resveratrol showed a yellowish brown color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 26 publications
5
26
1
Order By: Relevance
“…The packaging matrix chosen was poly(lactide) (PLA) because of its renewable character. The inclusion of natural antioxidants in PLA in the aim of developing an active material has already been suggested in literature [43][44][45]. Furthermore, some studies already exist pointing to the feasibility of inclusion of lignin into PLA [5,9,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…The packaging matrix chosen was poly(lactide) (PLA) because of its renewable character. The inclusion of natural antioxidants in PLA in the aim of developing an active material has already been suggested in literature [43][44][45]. Furthermore, some studies already exist pointing to the feasibility of inclusion of lignin into PLA [5,9,46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, PLA modified with natural origin compounds has been proposed as active packaging [8,23,24]. In this way, Hwang et al, (2011) proposed PLA with added α-tocopherol and resveratrol as promising active functional membranes [8]. Jamshidian et al, (2012) studied PLA with ascorbyl palmitate although they reported high loss of antioxidant during polymer preparation and negatives results on PLA transparency [24].…”
Section: Introductionmentioning
confidence: 99%
“…So, additives are require for transparent PLA films to block light transmission [22]. Furthermore, PLA modified with natural origin compounds has been proposed as active packaging [8,23,24]. In this way, Hwang et al, (2011) proposed PLA with added α-tocopherol and resveratrol as promising active functional membranes [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blending with the unsaponifiable compound !-tocopherol showed small gains in elongation at break, which extends already existing knowledge. It was already shown that the use of !-tocopherol as a natural antioxidant in PLA at small quantities (<4 wt%) induced a slightly T g decrease [74] but no increase in elongation at break [75]. Here, no elongation at break improvement upon was found using greater !-tocopherol amounts, despite solubility was assessed to be higher than other molecules (such as HPO and HCO, Table 4) and a T g decrease was observed (Table 3).…”
Section: Results and Discussion 31 Effects Of Free Fatty Acids Glymentioning
confidence: 63%